(untitled) (Annals of Medical Research, 2025)
Aim: This paper investigated the relationship between sexual health literacy (SHL) of young adults and attitudes toward sexual health. Materials and Methods: This study was descriptive and correlational in design. The sample size included 281 young adults. Data were collected using a personal information form, the Sexual Health Literacy Scale (SHLS), and the Sexual Health Attitude Scale (SHAS). The data were analyzed using the independent-samples t-test, one-way analysis of variance (ANOVA), Welch ANOVA test, Pearson’s correlation coefficients, and simple linear regression analysis. Results: Participants’ mean SHLS and SHAS scores were 59.60±10.86 and 149.68±12.43, respectively. Both SHLS and SHAS scores were significantly higher among women compared to men, and among those who had received sexual health education compared to those who had not (p<0.01). Participants with master’s or higher degrees had higher mean SHLS score than other groups (p<0.01). When examining sources of sexual health information, participants who learned from healthcare professionals, books, and personal experiences scored higher on SHLS than those who did not (p<0.01). For SHAS, participants who gained knowledge from friends/acquaintances, siblings, and personal experiences had higher mean score than others (p<0.01). A positive correlation was found between total SHLS scores and both total SHAS score and all SHAS subscale scores (p<0.05). Additionally, SHLS “sexual attitude” subscale score was positively correlated with total SHAS score and all SHAS subscale scores (p<0.05). Similarly, SHLS “sexual knowledge” subscale score showed a positive correlation with total SHAS score and all SHAS subscale scores, except for the “gender roles” subscale (p<0.05). Finally, SHAS score explained 19% of the variance in SHLS score (β=0.433, p<0.001). Conclusion: Sexual health attitude, higher education, being a woman, and having received sexual health education are important determinants of SHL. Young adults with reliable sources of information on sexual health have high levels of SHL.